ANALISIS SISTEM DU PONT SEBAGAI SALAH SATU ALAT UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN PROPERTY REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2010 - 2014) - Liliek Nur Sulistiyo; Diah Ayu Retno Asih (INVENTORY: JURNAL AKUNTANSI, 2017)
This study aims to determine how the Du Pont analysis system can be used as a tool to assess the financial performance of Property and Real Estate listed on the Stock Exchange 2010-2014. Du Pont Analysis System is Return On Ivestment (ROI) generated through the multiplication of the advantages of component - component sales as well as the efficient use of total assets in generating profits. The data used in this study was obtained from Companies Condensed Financial Statements Property and Real Estate in 2010 to 2014 issued by each of the companies concerned. The company's sample using purposive sampling, sample worth using as many as five companies. The analysis technique used to assess the financial performance of Property and Real Estate is a method of Du Pont System consists of three steps: (1) Determining the Total Asset Turnover (2) Net Profit Margin (3) Return On Investment (ROI). Based on the analysis using the Du Pont System for Property and Real Estate companies, 5 companies 4 companies which have a value below the average ROI. Analysis showed that the company PT.Ciputra Development Tbk were able to prove the performance of the company to generate profits, the better because it has above-average ROI of the company, ie 5.73%.Keywords : Total Asset Turnover, Net Profit Margin, Return Of Investment